A method for the preparation of nicotinamide-loaded regenerated cellulose fibers

CN122980052APending Publication Date: 2026-10-27BANGTE YUNXIAN (QINGDAO) NEW MATERIALS TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610805884.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-05
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

1、烟酰胺与再生纤维素纤维纺丝体系的相容性不佳:烟酰胺是极性小分子,虽然水溶性和亲水性好,但纤维素纤维纺丝体系粘度较大,小分子与再生纤维素高分子基体的相容性不佳,导致纺丝不稳定,纤维质量下降,且影响烟酰胺的负载均匀性和功能发挥

Benefits of technology

1、本发明制备的负载烟酰胺的再生纤维素纤维力学性能优异,其中干断裂强度2.3~2.47cN/dtex,湿断裂强度1.37~1.48cN/dtex;吸湿性好,回潮率大于15%。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure REF-OBJ-1780627676887-000001
    Figure REF-OBJ-1780627676887-000001
Patent Text Reader

Abstract

The present application relates to regenerated cellulose fiber technical field, specifically, it is a kind of preparation method of regenerated cellulose fiber loaded with nicotinamide, the preparation method includes viscose spinning dope preparation, preparation of precursor emulsion, blending, spinning and post-processing.The present application is by adding 3-cyanopyridine precursor solution in spinning dope, 3-cyanopyridine is wrapped in nascent fiber skeleton after spinning forming, 3-cyanopyridine is hydrolyzed to generate evenly distributed nicotinamide in bleaching process, so as to avoid a large amount of loss in coagulation bath.The present application is by crosslinking that the micropore of fiber surface is tightened, improves the wet strength of fiber, while greatly reducing the washing loss of nicotinamide in fiber, the loss rate of nicotinamide is less than 3% after washing 50 times.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of regenerated cellulose fiber technology, specifically, to a method for preparing regenerated cellulose fibers loaded with nicotinamide. Background Technology

[0002] With the rapid development of the textile industry towards functionalization, greening, and high-end products, functional fibers have become one of the core directions for the industry's transformation and upgrading. Among them, fiber products with additional functions such as skin care and health care are gradually becoming market hotspots due to their advantages of meeting the needs of human wearers and increasing product added value. Niacinamide, as an important active derivative of vitamin B3, has excellent water solubility, biocompatibility, and physiological activity. It is not only widely used in the cosmetics and pharmaceutical fields, but has also been gradually introduced into the textile industry in recent years. It has shown good application potential in improving the skin-friendliness of fibers and endowing fibers with whitening and moisturizing functions, providing new ideas for the research and development of functional fibers.

[0003] Currently, the application of nicotinamide in the textile industry mainly focuses on two areas: First, as a dye auxiliary or finishing agent component to improve dyeing and printing effects. Due to its neutral properties, nicotinamide can adjust the pH value of dyes and printing pastes, stabilize the dyeing system, enhance the affinity between dyes and fibers, improve dyeing uniformity, and reduce defects such as color spots and color variations. It is especially suitable for processing light-colored fabrics that are sensitive to color and light, and is compatible with natural fibers such as cotton, linen, and viscose, as well as synthetic fibers such as polyester and nylon. Second, as a functional active ingredient loaded into fibers to prepare functional textiles with skin care and health care functions. This type of application has been a research hotspot in recent years. Its core is to stably load nicotinamide into the inside or surface of fibers to achieve long-term sustained release during wear and fully exert its physiological activity.

[0004] In the preparation technology of nicotinamide-loaded fibers, existing technologies are mainly divided into three categories according to different loading methods: pre-spinning blending, post-finishing, and composite methods. Among them, pre-spinning blending has become the preferred method for loading functional components on natural polymer fibers such as regenerated cellulose fibers due to its advantages such as simple operation, uniform loading, and tight bonding with fibers.

[0005] However, in actual production operations, the following drawbacks exist: 1. Poor compatibility between nicotinamide and regenerated cellulose fiber spinning system: Nicotinamide is a polar small molecule. Although it has good water solubility and hydrophilicity, the viscosity of the cellulose fiber spinning system is relatively high. The small molecule has poor compatibility with the regenerated cellulose polymer matrix, which leads to unstable spinning, reduced fiber quality, and affects the uniformity of nicotinamide loading and its functional performance.

[0006] 2. Niacinamide is easily decomposed and its activity is reduced during the spinning process: Under the conditions of regenerated cellulose fiber spinning process, niacinamide is prone to structural changes, which leads to a reduction in its activity and makes it unable to fully exert its skin care, moisturizing and other functions.

[0007] 3. Difficulty in balancing nicotinamide loading and fiber mechanical properties: There is a clear contradiction between nicotinamide loading and fiber mechanical properties. If the loading is too high, the fiber mechanical properties will decrease significantly, failing to meet the needs of textile processing and actual wear; if the loading is too low, the expected functional effect cannot be achieved, making it difficult to achieve a balance between functionality and practicality.

[0008] 4. Poor long-term sustained-release performance of nicotinamide: Whether it is the finishing method or the pre-spinning blending method, due to the strong water solubility of nicotinamide, the nicotinamide loaded in the fiber is prone to rapid release during the washing process, resulting in serious loss of nicotinamide and poor functional durability of the fiber, making it impossible to achieve long-term stable functionality; although some technologies using microspheres, liposomes and other carriers can improve the sustained-release performance, there are problems such as poor compatibility between the carrier and the fiber, easy shedding or sudden release, and the process is complicated and costly.

[0009] Therefore, in the current textile industry, the technology for preparing fibers loaded with nicotinamide, especially the technology of adding nicotinamide before spinning regenerated cellulose fibers, still has defects such as unstable spinning, easy loss of nicotinamide in the coagulation bath, difficulty in balancing loading and mechanical properties, and poor long-term sustained-release effect. Summary of the Invention

[0010] The purpose of this invention is to provide a method for preparing regenerated cellulose fibers loaded with nicotinamide, which satisfies the functionality of the fiber while avoiding the loss of mechanical properties caused by the addition of functionality.

[0011] To achieve the above objectives, the present invention provides a method for preparing regenerated cellulose fibers loaded with nicotinamide, the method comprising the following steps: S1. Preparation of viscose spinning solution The pulp raw material is soaked, pressed, crushed, aged, yellowed, dissolved, filtered, defoamed, and matured to obtain spinning dope.

[0012] Preferably, the pulp raw material is one or more of wood pulp, cotton pulp, or bamboo pulp.

[0013] Preferably, the immersion temperature is 40-50°C, the time is 35-45 minutes, and the solution is sodium hydroxide solution with a mass fraction of 14-18%.

[0014] Preferably, the aging temperature is 20-25°C and the aging time is 2-3 hours.

[0015] Preferably, the chlorosis temperature is 15-20°C and the chlorosis time is 60-80 min.

[0016] Preferably, the dissolution is divided into two stages: the first stage is at a temperature of 20-25°C for 2-3 hours; the second stage is at a temperature of 10-15°C for 50-60 minutes.

[0017] Preferably, the maturation time is 18-24 hours and the maturation temperature is 15-20°C.

[0018] Preferably, the falling ball viscosity of the spinning solution is controlled at 50-65s, the maturity is controlled at 11-15mL (10% NH4Cl), the NaOH content is 4.2-4.7wt%, and the cellulose content is 7.4-8.2wt%.

[0019] S2, Preparation of precursor emulsion 3-Cyanopyridine and an emulsifier were added to deionized water and emulsified at high speed to obtain a precursor emulsion.

[0020] Preferably, the mass ratio of 3-cyanopyridine, emulsifier, and deionized water is 15-20:1-3:80-90.

[0021] Preferably, the high-speed emulsification temperature is 55-65°C, the time is 15-20 min, and the rate is 4000-5000 r / min.

[0022] S3, blending The precursor emulsion is added to the spinning solution by pre-spinning injection and stirred for 10-15 minutes to obtain the blended spinning solution.

[0023] Preferably, the amount of the precursor emulsion added is based on the fact that the 3-cyanopyridine in the precursor emulsion accounts for 5 to 7 wt% of the methyl cellulose content in the spinning solution.

[0024] Because nicotinamide is an extremely hydrophilic small molecule, if it is added directly during blending, a large amount of the small nicotinamide molecule will diffuse into the coagulation bath, resulting in a very high loss rate, wasting raw materials, and contaminating the coagulation bath. However, using an emulsion of 3-cyanopyridine, which is hydrophobic, results in almost no dissolution or loss in the coagulation bath and is encapsulated within the formed cellulose backbone. The mechanical properties of cellulose fibers depend on the tight hydrogen bond network formed between cellulose macromolecules during molding. If nicotinamide is used directly, the amide groups in nicotinamide will interfere with the hydrogen bonding between cellulose macromolecules, leading to a decrease in strength. However, using 3-cyanopyridine, which contains a cyano group and a nitrogen atom on the pyridine ring, without active hydrogen-donating groups, results in low interference with the bonding between cellulose macromolecules, ensuring the backbone strength of the nascent fiber bundle.

[0025] S4, spinning After the blended spinning solution is ejected through the spinneret, it is formed and drawn in the coagulation bath to obtain nascent fiber bundles; the nascent fiber bundles are further plasticized and shaped in a second bath to obtain fiber bundles.

[0026] Preferably, in the coagulation bath components, the sulfuric acid is 80-100 g / L, the zinc sulfate is 40-60 g / L, the sodium sulfate is 220-230 g / L, the reaction temperature is 40-45℃, the spinning rate is 35-45 m / min, and the draw is 10-20%.

[0027] Preferably, in the second bath, the concentration of sulfuric acid is 15-25 g / L, the temperature is 80-90°C, the draw ratio in the second bath is 80-90%, and the spinning rate is 35-45 m / min.

[0028] S5, Post-processing The fiber bundles are acid-washed, desulfurized, bleached, cross-linked, washed, oiled, and dried to obtain nicotinamide-loaded regenerated cellulose fibers.

[0029] Preferably, the desulfurization process uses sodium sulfite with a concentration of 15–30 g / L and a temperature of 70–80 °C.

[0030] Preferably, the bleaching process is carried out in a bleaching bath, wherein the components and concentrations in the bleaching bath are: 27.5% hydrogen peroxide 10-15 g / L, sodium carbonate 1-2 g / L, hydrogen peroxide stabilizer 2-3 g / L, penetrant 1-2 g / L; and the solvent is water.

[0031] Preferably, the temperature of the bleaching bath is 50-60°C, the bleaching time is 40-50 min, and the bath ratio is 1:15-20.

[0032] Preferably, the crosslinking process involves immersing the bleached fiber bundles in a crosslinking bath, followed by drying at 80–90°C for 50–60 minutes, and then continuing to dry at 120–125°C for 20–30 minutes, followed by washing with water until neutral to avoid citric acid residue; the components and concentrations in the crosslinking bath are: citric acid 40–50 g / L, sodium hypophosphite 10–15 g / L; and water as the solvent.

[0033] Preferably, the immersion temperature is 30-40°C, the immersion time is 5-7 minutes, and the bath ratio is 1:15-20.

[0034] In the bleaching process, hydrogen peroxide acts as both bleaching and oxidation agents, sodium carbonate provides a weakly alkaline environment, and the hydrogen peroxide stabilizer stabilizes both the hydrogen peroxide and the weakly alkaline environment. In the weakly alkaline oxidizing environment of the bleaching bath, 3-cyanopyridine hydrolyzes, generating uniform nicotinamide within the fiber. In the crosslinking process, the bleached fiber bundles are immersed in a crosslinking bath, followed by drying, where excess moisture is removed at 80–90°C. Citric acid contains three carboxyl groups; at 120–125°C, citric acid can form crosslinking bonds with the hydroxyl groups on the cellulose surface. Through crosslinking, the micropores on the fiber surface tighten, not only reducing the loss of nicotinamide during washing, but also improving the wet strength of the fiber through the formation of the crosslinked network structure. Furthermore, at this temperature, the fiber is less prone to yellowing and brittleness.

[0035] By adopting the above technical solution, the technical effect achieved by this invention is as follows: 1. The nicotinamide-loaded regenerated cellulose fiber prepared by this invention has excellent mechanical properties, with a dry breaking strength of 2.3-2.47 cN / dtex and a wet breaking strength of 1.37-1.48 cN / dtex; it also has good moisture absorption with a moisture regain of more than 15%.

[0036] 2. The loss rate of 3-cyanopyridine in the coagulation bath of this invention is less than 0.1%, while the loss rate of spinning after directly adding nicotinamide to the spinning solution is more than 50%, indicating that this invention significantly improves the utilization rate of raw materials.

[0037] 3. This invention tightens the micropores on the fiber surface through cross-linking, which greatly reduces the loss of nicotinamide inside the fiber during washing. After 50 washes, the loss rate of nicotinamide is less than 3%. Detailed Implementation

[0038] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0039] The sources of the main raw materials in the examples are as follows: 3-Cyanopyridine (99% effective ingredient content) was purchased from Liaocheng Xinli New Materials Co., Ltd. Tween-80 (99% active ingredient content) was purchased from Shandong Feihong New Materials Co., Ltd. 27.5% hydrogen peroxide (active ingredient content 27.5%) was purchased from Jinan Haicheng Chemical Co., Ltd. Sodium carbonate (99% effective ingredient content) was purchased from Zibo Linnuo Chemical Co., Ltd. Hydrogen peroxide stabilizer (99% effective ingredient content) was purchased from Jinan Haisheng Chemical Co., Ltd. The penetrant JFC (99% effective ingredient content) was purchased from Jinan Haisheng Chemical Co., Ltd. Citric acid (99% effective ingredient content) was purchased from Jinan Haisheng Chemical Co., Ltd. Sodium hypophosphite (99% effective ingredient content) was purchased from Jinan Haisheng Chemical Co., Ltd.

[0040] Example 1: A method for preparing regenerated cellulose fibers loaded with nicotinamide, the method comprising the following steps: S1. Preparation of viscose spinning solution Wood pulp is soaked, pressed, crushed, aged, xanthated, dissolved, filtered, defoamed, and matured to obtain spinning dope.

[0041] The immersion temperature was 45°C, the time was 40 minutes, and the solution was immersed in a 16% sodium hydroxide solution.

[0042] The aging temperature is 25℃ and the aging time is 2 hours.

[0043] The chlorosis temperature was 18℃ and the chlorosis time was 70 min.

[0044] The dissolution process is divided into two stages: the first stage is at a temperature of 20°C for 3 hours; the second stage is at a temperature of 10°C for 60 minutes.

[0045] The maturation time is 20 hours and the maturation temperature is 18°C.

[0046] The spinning solution has a falling ball viscosity of 60s, a maturity of 13mL (10% NH4Cl), a NaOH content of 4.5wt%, and a cellulose content of 7.8wt%.

[0047] S2, Preparation of precursor emulsion 3-Cyanopyridine and Tween-80 were added to deionized water and emulsified at high speed to obtain a precursor emulsion.

[0048] The mass ratio of 3-cyanopyridine, Tween-80, and deionized water is 18:2:85.

[0049] The high-speed emulsification was carried out at a temperature of 60°C for 17 minutes and at a rate of 4500 r / min.

[0050] S3, blending The precursor emulsion was added to the spinning solution by pre-spinning injection and stirred for 12 minutes to obtain the blended spinning solution.

[0051] The amount of the precursor emulsion added is based on the fact that the 3-cyanopyridine in the precursor emulsion accounts for 6 wt% of the methyl cellulose content in the spinning solution.

[0052] S4, spinning After the blended spinning solution is ejected through the spinneret, it is formed and drawn in the coagulation bath to obtain nascent fiber bundles; the nascent fiber bundles are further plasticized and shaped in a second bath to obtain fiber bundles.

[0053] The coagulation bath composition includes 80 g / L sulfuric acid, 60 g / L zinc sulfate, and 220 g / L sodium sulfate. The reaction temperature is 40°C, the spinning rate is 35 m / min, and the draw is 15%.

[0054] In the second bath, the concentration of sulfuric acid is 20 g / L, the temperature is 85°C, the draw ratio is 85%, and the spinning rate is 35 m / min.

[0055] S5, Post-processing The fiber bundles are acid-washed, desulfurized, bleached, cross-linked, washed, oiled, and dried to obtain nicotinamide-loaded regenerated cellulose fibers.

[0056] The desulfurization process uses sodium sulfite at a concentration of 22 g / L and a temperature of 75°C.

[0057] The bleaching process is carried out in a bleaching bath, the components and concentrations of which are: 27.5% hydrogen peroxide 13g / L, sodium carbonate 1.5g / L, hydrogen peroxide stabilizer 1g / L, penetrant JFC 1.5g / L, pH 9; and water as the solvent.

[0058] The bleaching bath temperature was 55℃, the bleaching time was 45 minutes, and the bath ratio was 1:20.

[0059] The crosslinking process involves immersing the bleached fiber bundles in a crosslinking bath, followed by drying at 85°C for 55 minutes, then drying at 125°C for another 25 minutes, and finally washing with water until neutral to avoid citric acid residue. The components and concentrations in the crosslinking bath are: citric acid 45 g / L, sodium hypophosphite 13 g / L, and water as the solvent.

[0060] The impregnation temperature was 35°C, the time was 6 minutes, and the liquor ratio was 1:20.

[0061] Example 2: A method for preparing regenerated cellulose fibers loaded with nicotinamide, the method comprising the following steps: S1. Preparation of viscose spinning solution Wood pulp is soaked, pressed, crushed, aged, xanthated, dissolved, filtered, defoamed, and matured to obtain spinning dope.

[0062] The immersion temperature was 40°C, the time was 35 minutes, and the solution was immersed in a 14% sodium hydroxide solution.

[0063] The aging temperature is 20℃ and the aging time is 3 hours.

[0064] The chlorosis temperature was 15℃ and the chlorosis time was 60 min.

[0065] The dissolution process is divided into two stages: the first stage is at a temperature of 20°C for 3 hours; the second stage is at a temperature of 10°C for 60 minutes.

[0066] The maturation time is 18 hours and the maturation temperature is 20°C.

[0067] The spinning solution has a falling ball viscosity of 50s, a maturity of 11mL (10% NH4Cl), a NaOH content of 4.2wt%, and a cellulose content of 7.4wt%.

[0068] S2, Preparation of precursor emulsion 3-Cyanopyridine and Tween-80 were added to deionized water and emulsified at high speed to obtain a precursor emulsion.

[0069] The mass ratio of 3-cyanopyridine, Tween-80, and deionized water is 15:1:80.

[0070] The high-speed emulsification was carried out at a temperature of 55°C for 20 minutes and at a rate of 4000 r / min.

[0071] S3, blending The precursor emulsion was added to the spinning solution by pre-spinning injection and stirred for 10 minutes to obtain the blended spinning solution.

[0072] The amount of the precursor emulsion added is calculated based on the percentage of 3-cyanopyridine in the precursor emulsion to 5 wt% of the methyl cellulose content in the spinning solution.

[0073] S4, spinning After the blended spinning solution is ejected through the spinneret, it is formed and drawn in the coagulation bath to obtain nascent fiber bundles; the nascent fiber bundles are further plasticized and shaped in a second bath to obtain fiber bundles.

[0074] The coagulation bath composition includes 100 g / L sulfuric acid, 40 g / L zinc sulfate, and 230 g / L sodium sulfate. The reaction temperature is 45°C, the spinning rate is 45 m / min, and the draw is 20%.

[0075] In the second bath, the concentration of sulfuric acid is 15 g / L, the temperature is 80°C, the draw ratio is 80%, and the spinning rate is 45 m / min.

[0076] S5, Post-processing The fiber bundles are acid-washed, desulfurized, bleached, cross-linked, washed, oiled, and dried to obtain nicotinamide-loaded regenerated cellulose fibers.

[0077] The desulfurization process uses sodium sulfite at a concentration of 15 g / L and a temperature of 70 °C.

[0078] The bleaching process is carried out in a bleaching bath, the components and concentrations of which are: 27.5% hydrogen peroxide 10g / L, sodium carbonate 1g / L, hydrogen peroxide stabilizer 0.8g / L, penetrant JFC 1g / L, pH 8.7; and water as the solvent.

[0079] The bleaching bath temperature is 50℃, the bleaching time is 40 minutes, and the bath ratio is 1:15.

[0080] The crosslinking process involves immersing the bleached fiber bundles in a crosslinking bath, followed by drying at 80°C for 60 minutes, then drying at 125°C for another 20 minutes, and finally washing with water until neutral to avoid citric acid residue. The components and concentrations in the crosslinking bath are: citric acid 40 g / L, sodium hypophosphite 10 g / L, and water as the solvent.

[0081] The impregnation temperature was 40°C, the time was 7 minutes, and the liquor ratio was 1:20.

[0082] Example 3: A method for preparing regenerated cellulose fibers loaded with nicotinamide, the method comprising the following steps: S1. Preparation of viscose spinning solution Wood pulp is soaked, pressed, crushed, aged, xanthated, dissolved, filtered, defoamed, and matured to obtain spinning dope.

[0083] The immersion temperature was 50°C, the time was 45 minutes, and the solution was immersed in a sodium hydroxide solution with a mass fraction of 18%.

[0084] The aging temperature is 25℃ and the aging time is 2 hours.

[0085] The chlorosis temperature was 20℃ and the chlorosis time was 60 min.

[0086] The dissolution process is divided into two stages: the first stage is at a temperature of 25°C for 2 hours; the second stage is at a temperature of 15°C for 50 minutes.

[0087] The maturation time is 24 hours and the maturation temperature is 15°C.

[0088] The falling ball viscosity of the spinning solution is controlled at 65s, the maturity is controlled at 15mL (10% NH4Cl), the NaOH content is 4.7wt%, and the methyl cellulose content is 8.2wt%.

[0089] S2, Preparation of precursor emulsion 3-Cyanopyridine and Tween-80 were added to deionized water and emulsified at high speed to obtain a precursor emulsion.

[0090] The mass ratio of 3-cyanopyridine, Tween-80, and deionized water is 20:3:90.

[0091] The high-speed emulsification was carried out at a temperature of 65°C for 15 minutes and at a rate of 5000 r / min.

[0092] S3, blending The precursor emulsion was added to the spinning solution by pre-spinning injection and stirred for 15 minutes to obtain the blended spinning solution.

[0093] The amount of the precursor emulsion added is based on the fact that the 3-cyanopyridine in the precursor emulsion accounts for 7 wt% of the methyl cellulose content in the spinning solution.

[0094] S4, spinning After the blended spinning solution is ejected through the spinneret, it is formed and drawn in the coagulation bath to obtain nascent fiber bundles; the nascent fiber bundles are further plasticized and shaped in a second bath to obtain fiber bundles.

[0095] The coagulation bath composition includes 90 g / L sulfuric acid, 50 g / L zinc sulfate, and 225 g / L sodium sulfate. The reaction temperature is 45°C, the spinning rate is 40 m / min, and the draw is 10%.

[0096] In the second bath, the concentration of sulfuric acid is 25 g / L, the temperature is 90℃, the draw ratio is 90%, and the spinning rate is 40 m / min.

[0097] S5, Post-processing The fiber bundles are acid-washed, desulfurized, bleached, cross-linked, washed, oiled, and dried to obtain nicotinamide-loaded regenerated cellulose fibers.

[0098] The desulfurization process uses sodium sulfite at a concentration of 30 g / L and a temperature of 80 °C.

[0099] The bleaching process is carried out in a bleaching bath, the components and concentrations of which are: 27.5% hydrogen peroxide 15g / L, sodium carbonate 2g / L, hydrogen peroxide stabilizer 1.2g / L, penetrant JFC 2g / L, pH 9.4; and water as the solvent.

[0100] The bleaching bath temperature is 60℃, the bleaching time is 40 minutes, and the bath ratio is 1:17.

[0101] The crosslinking process involves immersing the bleached fiber bundles in a crosslinking bath, then drying them at 90°C for 50 minutes, followed by drying at 120°C for another 30 minutes, and finally washing them with water until neutral to avoid citric acid residue. The components and concentrations in the crosslinking bath are: citric acid 50 g / L, sodium hypophosphite 15 g / L, and water as the solvent.

[0102] The impregnation temperature was 30°C, the time was 5 minutes, and the liquor ratio was 1:15.

[0103] Comparative Example 1: The precursor emulsion of step S2 was removed, and 3-cyanopyridine in step S2 was replaced with nicotinamide. All other steps were the same as in Example 1. This was used as Comparative Example 1.

[0104] Comparative Example 2: The crosslinking step of S5 was removed, and the rest was the same as in Example 1, which served as Comparative Example 2.

[0105] The regenerated cellulose fibers prepared in Examples 1-3 and Comparative Examples 1-2 were subjected to performance testing, as detailed in Table 1.

[0106] Table 1 As can be seen from Table 1, the regenerated cellulose fibers loaded with nicotinamide prepared using Examples 1-3 have excellent mechanical properties, especially wet strength, and excellent moisture absorption effect, and the nicotinamide is more stable over a longer period of time.

[0107] In Example 1, the loss rate of 3-cyanopyridine in the coagulation bath was only 0.05%, while the fibers prepared in Comparative Example 1 not only showed a decrease in strength, but also experienced a loss rate of over 50% of nicotinamide in the coagulation bath after adding nicotinamide to the spinning solution, resulting in a decrease in moisture regain. Although Comparative Example 1 retained crosslinking, the dissolution of nicotinamide in the coagulation bath increased internal defects in the nascent fiber bundles, resulting in a loose internal fiber structure and thus a decrease in strength; furthermore, the loose internal structure led to insufficient encapsulation of nicotinamide, thus increasing the water washing loss rate.

[0108] While the strength of Comparative Example 2 decreased, the water wash loss rate of nicotinamide increased significantly, indicating that Example 1, by tightening the micropores on the fiber surface through crosslinking, significantly reduced the water wash loss of nicotinamide inside the fiber and improved the wet strength of the fiber. In the example, by controlling the components in the crosslinking bath at appropriate concentrations and times, crosslinking only occurred on the fiber surface. Although this crosslinking made the fiber surface brittle, it also compensated for the porosity defects on the fiber surface, making the stress distribution on the fiber surface more uniform. Therefore, the dry strength did not decrease and even slightly increased.

[0109] Unless otherwise specified, all proportions and percentages mentioned in this invention are mass proportions and mass percentages; all raw materials are commercially available.

[0110] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely preferred examples and are not intended to limit the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing regenerated cellulose fibers loaded with nicotinamide, characterized in that, The preparation method includes the preparation of viscose spinning solution, the preparation of precursor emulsion, blending, spinning and post-treatment. The precursor emulsion is prepared by adding 3-cyanopyridine and an emulsifier to deionized water and emulsifying at high speed to obtain the precursor emulsion. The blending process involves adding the precursor emulsion to the spinning solution using a pre-spinning injection method and stirring for 10–15 minutes to obtain a blended spinning solution.

2. The method for preparing regenerated cellulose fiber loaded with nicotinamide according to claim 1, characterized in that, The viscose spinning solution is prepared by impregnating, pressing, crushing, aging, xanthating, dissolving, filtering, degassing, and maturing pulp raw materials to obtain the spinning solution.

3. The method for preparing regenerated cellulose fiber loaded with nicotinamide according to claim 1, characterized in that, The mass ratio of 3-cyanopyridine, emulsifier and deionized water is 15-20:1-3:80-90; The high-speed emulsification is carried out at a temperature of 55–65°C, for a time of 15–20 min, and at a rate of 4000–5000 r / min.

4. The method for preparing regenerated cellulose fiber loaded with nicotinamide according to claim 1, characterized in that, The amount of the precursor emulsion added is based on the fact that the 3-cyanopyridine in the precursor emulsion accounts for 5 to 7 wt% of the methyl cellulose content in the spinning solution.

5. The method for preparing regenerated cellulose fiber loaded with nicotinamide according to claim 1, characterized in that, The spinning process involves the blended spinning solution being ejected through a spinneret and then formed and drawn in a coagulation bath to obtain nascent fiber bundles; the nascent fiber bundles are further plasticized and shaped in a second bath to obtain fiber bundles.

6. The method for preparing regenerated cellulose fiber loaded with nicotinamide according to claim 5, characterized in that, The coagulation bath composition includes 80–100 g / L sulfuric acid, 40–60 g / L zinc sulfate, and 220–230 g / L sodium sulfate; the reaction temperature is 40–45 °C; the spinning rate is 35–45 m / min; and the draw is 10–20%. In the second bath, the concentration of sulfuric acid is 15-25 g / L, the temperature is 80-90℃, the draw ratio is 80-90%, and the spinning rate is 35-45 m / min.

7. The method for preparing regenerated cellulose fiber loaded with nicotinamide according to claim 1, characterized in that, The post-processing involves acid washing, desulfurization, bleaching, cross-linking, water washing, oiling, and drying of the fiber bundles to obtain nicotinamide-loaded regenerated cellulose fibers. The desulfurization process uses sodium sulfite at a concentration of 15–30 g / L and a temperature of 70–80 °C.

8. The method for preparing regenerated cellulose fiber loaded with nicotinamide according to claim 7, characterized in that, The bleaching process is carried out in a bleaching bath, and the components and concentrations in the bleaching bath are as follows: 27.5% hydrogen peroxide 10-15 g / L, sodium carbonate 1-2 g / L, hydrogen peroxide stabilizer 2-3 g / L, penetrant 1-2 g / L; the solvent is water. The temperature of the bleaching bath is 50-60℃, the bleaching time is 40-50 minutes, and the bath ratio is 1:15-20.

9. The method for preparing regenerated cellulose fiber loaded with nicotinamide according to claim 7, characterized in that, The crosslinking process involves immersing the bleached fiber bundles in a crosslinking bath, then drying them at 80–90°C for 50–60 minutes, followed by drying at 120–125°C for another 20–30 minutes, and finally washing them with water until neutral. The components and concentrations in the crosslinking bath are: citric acid 40–50 g / L, sodium hypophosphite 10–15 g / L, and water as the solvent.

10. The method for preparing regenerated cellulose fiber loaded with nicotinamide according to claim 9, characterized in that, The impregnation temperature is 30-40°C, the time is 5-7 minutes, and the bath ratio is 1:15-20.